Knowledge and attitudes of undergraduate nursing students regarding dependent persons' oral health - Isabel de Jesus Oliveira; Dalila Santos Coelho; Andrea Godinho Silva; Ana Filipa Terra França; Germano Rodrigues Couto (Instituto Politécnico de Viseu, 2023)
Introduction: Nurses play a crucial role in maintaining and promoting oral health. Evidence suggests that nurses do not prioritize oral care, have insufficient knowledge, and have had no training in this area during their undergraduate training. Objectives: To evaluate nursing students' knowledge and attitudes toward oral hygiene in dependent patients. Methods: Observational and descriptive study, with data collection using an online self-completion questionnaire applied to 51 fourth-year undergraduate nursing students. Data regarding knowledge, attitudes, and practices, presented as frequencies, means, and standard deviation, were treated using SPSS, version 21. Results: Mean knowledge and attitudes of the participants were respectively 11.37 out of a maximum of 22 and 35.65 out of a maximum of 60. Conclusion: Participants value oral health in caring for hospitalized dependent patients; however, their knowledge and attitudes could be improved; thus, the need for research in this area emerges.